Does Environmental Governance matter for FDI? Testing for Pollution Haven Hypothesis for Indian States - Vinish Kathuria (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2016)
This paper tries to see the role of the actual expenditure on pollution and control equipment in a particular State on the location choice of foreign firms in India. Based on Levinson (2001), we compute Industry-adjusted pollution abatement expenditure index for 25 States for different time periods using Annual Survey of Industries data to see if FDI inflow is affected by any variation in pollution abatement expenditure (reflecting environmental governance). The index compares the actual pollution abatement expenditure in a particular State, unadjusted for industrial composition, to the predicted abatement expenditure in the same State (where the predictions are based on nationwide abatement expenditures by industry and each State's industrial composition). If adjusted index is low for a State, this implies that the State has poor environmental governance and this would induce foreign firms to invest. In other words, our study tests for 'pollution haven' hypothesis. Our results do not find any evidence of pollution haven hypothesis for 21 Indian States. Other variables are more important in influencing foreign firms' decision than environmental stringency.
hdl:10398/9289
Keywords: 330; Pollution haven hypothesis; India; Abatement expenditure; Environmental governance; Auslandsinvestition; Umweltkosten; Umweltstandard; Teilstaat; Indien